Implementation of News Based Online Learning to Increase Students' Motivation and Critical Thinking Ability on the Study of Ekology - Marlina, Selly; Ridlo, Saiful; Partaya, Partaya (Universitas Negeri Semarang)
Teacher-centered learning makes students feel unmotivated to learning without the latest innovations in learning. Especially during Covid-19 virus pandemic that makes educational institutions have to dismiss students and make teachers need innovation with new online learning. There needs to be change in the learning process that can arouse student’s motivation. Motivation can affect students' critical thinking abilities. The purpose of this study is to analyze differences and enhancement of motivation and critical thinking abilities between group of students who apply of news based online learning compared with not as the control group. This research is a quasi-experimental research with a quantitative approach. The sample of this research are taken through randomize sampling. The results of the t-test showed significant different (sig. 0.01) of motivation between the classes that applied news based online learning with control classes. T-test results also showed significant different in critical thinking (sig. 0.00). N-Gain of motivation for the experimental group was 0.31 while the control group was 0.12. Meanwhile, N-Gain of critical thinking in the experimental group was 0.67, while the control group was 0.33. The results indicate that the application of the news-based online learning can increase students' motivation and critical thinking. Students who were taught with news-based online learning are more active in expressing their opinions and they are eager to participate in learning activities.